2012
DOI: 10.1007/s10840-012-9756-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of total atrial conduction time measured with tissue Doppler imaging for postoperative atrial fibrillation after coronary artery bypass surgery

Abstract: In this study, LA maximum volume and PA-TDI duration were found to be the independent predictors of the development of POAF after CABG. Echocardiographic predictors of left atrial electromechanical dysfunction may be useful in risk stratifying of patients in terms of POAF development after CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
5
22
0
1
Order By: Relevance
“…22 Recently, Özlü et al showed that LA maximum volume and PA-TDI duration were independent predictors of POAF development after conventional CABG. 23 The new information provided in the present study is that PA-TDI duration is also an independent predictor of POAF in patients undergoing OPCAB.…”
Section: Resultssupporting
confidence: 49%
“…22 Recently, Özlü et al showed that LA maximum volume and PA-TDI duration were independent predictors of POAF development after conventional CABG. 23 The new information provided in the present study is that PA-TDI duration is also an independent predictor of POAF in patients undergoing OPCAB.…”
Section: Resultssupporting
confidence: 49%
“…26 Recently, Özlü et al showed that the LA maximum volume and PA-TDI duration were independent predictors of POAF after conventional CABG. 27 The new information from our previous study was that the PA-TDI duration was also an independent predictor of POAF in patients undergoing offpump CABG. 9 The aim of the present study was to determine the optimal cutoff value of PA-DTI duration to predict POAF.…”
Section: Study Limitationsmentioning
confidence: 95%
“…16 Recently, Özlü et al showed that LA maximum volume and PA-TDI duration were independent predictors of POAF after conventional CABG. 19 Our previous studies also showed that PA-TDI duration was an independent predictor of POAF in patients undergoing off-pump CABG and aortic valve surgery. 7, 8 The aim of the present study was to determine the optimal cut-off of PA-TDI duration to predict POAF in patients with MR.…”
Section: Preoperative Ecg and Echocardiographymentioning
confidence: 80%